Socioeconomic determinants of frequency of fish purchasing among Trinidad and Tobago shoppers: A binary logit analysis - Iton, C. W. Ardon; Hutchinson, Sharon D. (Applied Studies in Agribusiness and Commerce, 2017)
As the Caribbean continues to succumb to the pressure of Non-Communicable Diseases innovative strategies are being sought to rectify the problem. Increasing the purchase and consumption of fish/seafood has great potential in this regard; however, very little empirical research appears to have been undertaken on food marketing in general and for fish in particular in the Caribbean. This study analyzed the factors that affect the frequency of fish purchasing in Trinidad and Tobago. The results of the analysis indicated that 63% of the sample are occasional purchasers of fish (purchased fish less frequently than once per week). The binary logit analysis showed that of the eight socioeconomic variables analyzed, only three were statistically significant – age, educational level attained and religion. The results suggested that persons over 35 years, more educated (tertiary level trained) and non-Christians are more probable to be regular purchasers of fish than younger, primary and secondary level educated Christians. It is hoped that marketers trying to develop strategies to gain market share in the highly competitive food market, nutritionists and others attempting to reduce the health care costs of Trinidad and Tobago and other Caribbean countries through the increased consumption of fish/seafood find these results informative.JEL. Code: M31, Q13, C25